Research activities on next-generation mobile communications and services in Korea. - Ryu, Seungwan (IEEE Communications magazine)
In this article we present a perspective on next-generation mobile communications and services. As a preliminary research work on next-generation mobile communications, we exploit what next-generation mobile services will be (S. Ryu et al., May 2003). We define next-generation mobile services as a hierarchy of services consisting of three different service levels: the service areas, the service functionalities, and the service technologies. We derive these service levels by means of scenario-based analysis. Next we propose conceptual reference network architecture, focusing on the realization of the service technologies. We divide the network into four different parts: a user equipments and access part, a network service provisioning layer part, a network control layer part, and non-mobile network operator service pan, according to characteristics of information and service flows within a network. In this reference network architecture, service elements such as servers, processors, and gateways are placed in each network part to support the derived next-generation mobile services. Finally, we give a brief introduction of research and development activities for next-generation mobile communication systems and services in Korea.